History and Evolution of Social Assistance in Indonesia - World Bank (Washington, DC, 2013)
Over the past 13 years, the Government of Indonesia (GOI) has moved from a set of temporary, crisis-driven social assistance initiatives towards a more permanent system of social assistance programs. This background paper aims to provide a brief history of the major developments in the GOI's household-targeted social assistance policy and programs with more limited discussion of supply-side and community social assistance initiatives. The note is organized chronologically with developments in social assistance presented together with information about the economic, political and social contexts in which these developments occurred. Indonesia's economic growth was also associated with substantial declines in the poverty, especially among rural households. The poverty headcount fell from 54.2 million to 34.5 million Indonesians and poverty incidence fell from 41.1 to 17.7 percent. While poverty reduction was not a policy objective in GOI documents until the early 1990s, the GOI's agricultural and rural development strategies and commitment to human capital investment through financing and provision of education and health services also contributed to poverty reduction. Furthermore, the GOI intervened in staple foods markets for the purpose of reducing domestic price volatility and increasing food security. During this era, when individuals or families employed in the informal sector required in-kind or financial assistance, they sought it from extended families, communities, or informal credit markets.